Representation of Family Law in the Digital Space: A Study of Discourse Analysis on Instagram Accounts - Amri, Amri; Aminah, Siti; Janah, Sidanatul; Utama, Yopi Yudha; Dewi, Dwi Ratna Cinthya (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
The emergence of interesting content through Instagram accounts managed by a person or a certain group representing a family law is important to discuss. One of the discourses that appears in these contents is related to the advice of husband and wife in building their household, then brings up tips for husband and wife to pay attention to each other. The husband and wife can apply the contents which are posted on the instagram account to create a harmonious household life. This paper aims to see the narratives that appear in the posts of intagram accounts through a discourse analysis approach. This research data is focused on 3 Instagram accounts with a selection of many followers on the Instagram account. The 3 Instagram accounts are @suami.istri.bahagia, @nasihatsuamiistri, @suamiistriromantis. This research leads to Netnographic studies or digital-based research. Then, because the data obtained is in the form of written content narratives, pamphlets, and videos posted on Instagram, it will be analyzed using discourse theory. The results showed that the content of the program gave rise to two studies that represented family law. First, it relates to the husband's obligation to the wife and the wife's obligation to the husband by posting content in the form of advice for the husband and wife. Second, post content about parents' obligations to children by posting narratives in the form of tips and procedures. Furthermore, the author found that the problem that occurs in these Instagram accounts is the existence of gender bias, this means that posts that represent family law are more content intended for the Wife and their content reflects the business of selling Products.